Local vs. national: Epidemiology of pedestrian injury in a mid-Atlantic city. (19th May 2018) - Nesoff, Elizabeth D.; Pollack, Keshia M.; Knowlton, Amy R.; Bowie, Janice V.; Gielen, Andrea C.
ABSTRACT: Objective : Understanding pedestrian injury trends at the local level is essential for program planning and allocation of funds for urban planning and improvement. Because we hypothesize that local injury trends differ from national trends in significant and meaningful ways, we investigated citywide pedestrian injury trends to assess injury risk among nationally identified risk groups, as well as identify risk groups and locations specific to Baltimore City. Methods : Pedestrian injury data, obtained from the Baltimore City Fire Department, were gathered through emergency medical services (EMS) records collected from January 1 to December 31, 2014. Locations of pedestrian injuries were geocoded and mapped. Pearson's chi-square test of independence was used to investigate differences in injury severity level across risk groups. Pedestrian injury rates by age group, gender, and race were compared to national rates. Results : A total of 699 pedestrians were involved in motor vehicle crashes in 2014—an average of 2 EMS transports each day. The distribution of injuries throughout the city did not coincide with population or income distributions, indicating that there was not a consistent correlation between areas of concentrated population or concentrated poverty and areas of concentrated pedestrian injury. Twenty percent ( n = 138) of all injuries occurred among children age ≤14, and 22% ( n = 73) of severe injuries occurred among young children. The rate of injury in this age group was 5 times the national rate (Incident Rate Ratio [IRR] = 4.81, 95% confidence interval [CI], [4.05, 5.71]). Injury rates for adults ≥65 were less than the national average. Conclusions : As the urban landscape and associated pedestrian behavior transform, continued investigation of local pedestrian injury trends and evolving public health prevention strategies is necessary to ensure pedestrian safety.